The modern search for the real Jesus an introductory survey of the historical roots of Gospels criticism - Strimple, Robert B. 1935- (Phillipsburg, NJ Presbyterian and Reformed, 1995)
Includes bibliographical references and index.
Keywords: Bible. N.T. Gospels -- criticism, interpretation, etc. -- history